Studies on implementation of national special education policy in the perspective of inclusive education - PNEEPEI in brazilian municipalities - Ribas, Geovania Fagundes; Pires, Ennia Débora Passos Braga; Araújo, Silvânia Brito (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
This article aims to make a survey of the studies regarding the implementation of the National Policy of Special Education in the Inclusive Education Perspective - PNEEPEI, produced from 2008 to 2017, in order to discover actions that enable the construction of a truly education. inclusive and how municipalities are organizing to make them effective. This is a bibliographical research, with qualitative approach, which had as methodological path: survey of productions; selection of those closest to the theme, systematization of information and organization of results. The search for the productions was carried out in the CAPES Thesis and Dissertation Bank (Coordination for the Improvement of Higher Education Personnel) and for the data analysis, thematic categories were elaborated. The results showed positive experiences in the implementation of the policy, although in a smaller number that indicate difficulties and reveal the contribution of the dissemination of these actions to the implementation of PNEEPEI throughout the country.